Evaluation of a computer‐assisted letter sound tutoring program: An application to preschool English language learners. Issue 3 (9th August 2022) - Long, Stephanie; Volpe, Robert J.; Briesch, Amy M.
Abstract: The importance of letter sound knowledge (LSK) as a precursor to later literacy skills has been well‐documented. Since English language learners (ELLs), or students who first acquired a language other than English, continue to underperform in reading compared to their English‐speaking peers, they are particularly at‐risk for reading and academic difficulties. The current study examines the utility and acceptability of teaching letter sounds to four ELL preschoolers through a software‐based incremental rehearsal tool (Tutoring Buddy). All students demonstrated increases in LSK, with large effect sizes derived through percentage of all nonoverlapping data analyses. Increases were also noted in the students' generalization of letter sounds to measures of letter sound fluency and nonsense word fluency, signified by small to large effect sizes. Large effect sizes generated for real word fluency measures indicated that all students were able to apply LSK to decoding real, consonant‐vowel‐consonant words. All students rated Tutoring Buddy as helpful for their letter sound learning, and varied in how enjoyable they found the intervention to be. Overall, the results support the use of Tutoring Buddy as an effective and acceptable method for teaching letter sounds to young ELLs. Implications for school‐based professionals working with ELL and future directions for research are discussed. Practitioner points: Tutoring Buddy was highly effective in improving student letter‐sound knowledge and fluency in word reading. All of the English language learners (ELL) student participants rated Tutoring Buddy as helpful for their learning of letter sounds. Overall, Tutoring Buddy is an effective and acceptable method for teaching letter sounds to young ELL.